SOCIOECONOMIC LIFE IN THE BUKHARA KHANATE IN THE 16TH CENTURY (Academia Science Repository, 2023)
Bush , in this article, in the 16th century, the social and economic life of the Bukharan Khanate, the reforms carried out by the Shaybanids, the administration of the state under the Shaybanids, were given details about their economic life.